Karakterisasi Batubara Formasi Walanae Daerah Kaloling Kabupaten Sinjai Propinsi Sulawesi Selatan - Anshariah Anshariah; Emi Prasetyawati Umar; Agus Ardianto Budiman; Hasbi Bakri; Alam Budiman Thamsi; Nurliah Jafar; Alfian Nawir; Andi Fadli Heriansyah; Muhamad Hardin Wakila; F Firdaus; Harwan Harwan (Universitas Muslim Indonesia, 2022)
Coal is a unique sedimentary rock, both in the process of formation and rock characteristics which are strongly influenced by the conditions of the depositional environment. Different depositional environments, the characteristics of the coal are different. The research method used in this research in the field is in the form of direct sampling in the field using the channel sampling ply by ply method, namely sampling by making channels on coal outcrops and taking samples that represent the lower, middle and upper layers of the coal seam to determine the average characteristics. The sample is then prepared to get a certain size and can be representative of the field sample. The prepared samples were then subjected to a proximate test to determine the moisture content, ash content, volatile matter and fixed carbon. Laboratory tests are carried out in the Lab. Analysis and Processing Hasanuddin University Makassar. The results of the proximate analysis carried out show the coal characteristics of the Walanae Formation in the Kaloling Region which has a moisture content value that decreases from bottom to top with an average of 7.49%; coal ash content increased from bottom to top with an average value of 47.63% ash content; the value of volatile matter decreased from bottom to top with an average of 26.56% of volatile matter; and the value of fixed carbon which increases with increasing depth with an average value of 18.29%.